Carbohydrates and insulin resistance in clinical nutrition: Recommendations from the ESPEN expert group. Issue 2 (April 2017) - Barazzoni, R.; Deutz, N.E.P.; Biolo, G.; Bischoff, S.; Boirie, Y.; Cederholm, T.; Cuerda, C.; Delzenne, N.; Leon Sanz, M.; Ljungqvist, O.; Muscaritoli, M.; Pichard, C.; et al.
Summary: Growing evidence underscores the important role of glycemic control in health and recovery from illness. Carbohydrate ingestion in the diet or administration in nutritional support is mandatory, but carbohydrate intake can adversely affect major body organs and tissues if resulting plasma glucose becomes too high, too low, or highly variable. Plasma glucose control is especially important for patients with conditions such as diabetes or metabolic stress resulting from critical illness or surgery. These patients are particularly in need of glycemic management to help lessen glycemic variability and its negative health consequences when nutritional support is administered. Here we report on recent findings and emerging trends in the field based on an ESPEN workshop held in Venice, Italy, 8–9 November 2015. Evidence was discussed on pathophysiology, clinical impact, and nutritional recommendations for carbohydrate utilization and management in nutritional support. The main conclusions were: a) excess glucose and fructose availability may exacerbate metabolic complications in skeletal muscle, adipose tissue, and liver and can result in negative clinical impact; b) low-glycemic index and high-fiber diets, including specialty products for nutritional support, may provide metabolic and clinical benefits in individuals with obesity, insulin resistance, and diabetes; c) in acute conditions such as surgery and critical illness, insulin resistance and elevated circulating glucose levels have a negative impact on patient outcomes and should be prevented through nutritional and/or pharmacological intervention. In such acute settings, efforts should be implemented towards defining optimal plasma glucose targets, avoiding excessive plasma glucose variability, and optimizing glucose control relative to nutritional support.